Furnitecture : furniture that transforms space - Yudina, Anna (London : Thames & Hudson, 2024)
A compact sourcebook of ideas for innovative furnishing, interior environments and small-scale architectural interventions. As the definition of 'designer' expands and architects today create everything from jewelry to urban masterplans, a new wave of objects is transforming our interior spaces.
1. Experimenting with structure. -- Frameworks -- Deconstruction -- Blocks & modules -- Stacks and towers -- Transformers -- Parametrics. 2. Furniture as micro-architecture. -- Fusion -- Space organizers -- Room in a room -- In-built -- Landscapes. 3. Synthesis. -- Macro-furniture -- Architectural shelving -- Partitions -- Plug-ins & add-ons -- Building blocks -- Multi-scale.
Includes bibliographic references and index.
Keywords: FURNITURE DESIGN--HISTORY--21ST CENTURY; FURNITURE DESIGN--HISTORY--20TH CENTURY; SPACE (ARCHITECTURE)